Hypoglycaemia begets hypoglycaemia. (28th June 2013) - Arora, Alok
Abstract : Drug-induced (insulin/insulin secretagogue) hypoglycaemia is the most common cause of hypoglycaemia particularly in the elderly. It is estimated that hypoglycaemia of any severity occurs annually in 5–20% of patients taking antihyperglycaemic agents. Although these hypoglycaemic episodes are rarely fatal, they can be associated with serious clinical sequelae. The half-life for most sulfonylurea medications is 14–16 h; they can cause severe, prolonged hypoglycaemia. It is important to recognise, prevent and treat hypoglycaemic episodes secondary to the use of antihyperglycaemic agents. Patient education has become focused on minimising hyperglycaemia but emphasis must be placed on minimising even minor subclinical hypoglycaemia because it will contribute to a vicious cycle of hypoglycaemia begetting hypoglycaemia. Ten per cent dextrose is recommended for the reversal of all hypoglycaemic episodes rather than the conventional 50% dextrose. Octreotide can be an option for recurrent and relapsing hypoglycaemia in an acute setting.